1996
DOI: 10.1046/j.1365-2249.1996.d01-794.x
|View full text |Cite
|
Sign up to set email alerts
|

Low T cell reactivity to combined CD3 plus CD28 stimulation is predictive for progression to AIDS: correlation with decreased CD28 expression

Abstract: SUMMARYIn 219 HIV-1-infected men of the Amsterdam cohort we measured CD4 T cell numbers and in vitro T cell responses to CD3 MoAbs with or without CD28 costimulation and phytohaemagglutinin (PHA). The value of these markers was estimated for disease progression within 4 years. CD28 expression on T cells has been related to T cell responses. CD28 costimulation considerably enhanced T cell reactivity ( 8-10-fold) with lower coefficients of variation compared with reactivity to CD3 MoAb alone (median 5 versus 20)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
12
1
1

Year Published

1998
1998
2010
2010

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 23 publications
2
12
1
1
Order By: Relevance
“…CD8 lymphocytosis, which is commonly seen in HIV-seropositive individuals, consists of CD28 Ϫ cells expressing activation markers such as HLA-DR, CD38, and CD45RO [29,30]. We observed a decrease in CD8 ϩ CD28 Ϫ T cells during HAART.…”
Section: Discussionmentioning
confidence: 56%
“…CD8 lymphocytosis, which is commonly seen in HIV-seropositive individuals, consists of CD28 Ϫ cells expressing activation markers such as HLA-DR, CD38, and CD45RO [29,30]. We observed a decrease in CD8 ϩ CD28 Ϫ T cells during HAART.…”
Section: Discussionmentioning
confidence: 56%
“…It has been reported that T-cell proliferation in response to stimulation with CD3 and CD3ϩCD28 MAbs decreases shortly after seroconversion, before the decline in CD4 ϩ T-cell number is observed (10,23,33). It has also been demonstrated that loss of T-cell reactivity to CD3 and CD3ϩCD28 MAbs in vitro is a strong predictive marker for progression to AIDS, independent of decline in CD4 counts (32,33). Thus, T-cell proliferative capacity is an important independent predictor of progression to HIV disease (31,33) and also can serve to monitor immunological improvement after therapy (1,26).…”
Section: Human Immunodeficiency Virus (Hiv) Infection Results In a Simentioning
confidence: 99%
“…It has been demonstrated that low levels of CD4 + CD28 + cells and a low T cell reactivity to CD3/CD28 costimulation predict AIDS [3,18]. Furthermore, the CD4 + CD28 + cell level correlates negatively with various HIV disease progression markers [4].…”
mentioning
confidence: 99%